2015
DOI: 10.1016/j.ultsonch.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemistry and bubble dynamics

Abstract: The details of bubble behaviour in chemically active cavitation are still not sufficiently well understood. Here we report on experimental high-speed observations of acoustically driven single-bubble and few-bubble systems with the aim of clarification of the connection of their dynamics with chemical activity. Our experiment realises the sonochemical isomerization reaction of maleic acid to fumaric acid, mediated by bromine radicals, in a bubble trap set-up. The main result is that the reaction product can on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 17 publications
1
42
1
Order By: Relevance
“…Calculations with a spherical bubble model can reproduce the essentials of the observed motion. Future experiments might establish firm links between the reported translation-induced jetting mode of bubble collapse, the related specific acoustic emission features, and nonvolatile liquid-phase sonochemistry [34].…”
Section: Discussionmentioning
confidence: 87%
“…Calculations with a spherical bubble model can reproduce the essentials of the observed motion. Future experiments might establish firm links between the reported translation-induced jetting mode of bubble collapse, the related specific acoustic emission features, and nonvolatile liquid-phase sonochemistry [34].…”
Section: Discussionmentioning
confidence: 87%
“…In addition to translation induced jetting (P-III) or surface mode instabilities (P-II), other liquid injection scenarios might be based on bubble splitting [44] or coalescence [45]. From the observations, extended fragmentation of P-III bubbles during collapse can be excluded apart from the potential ejection of the P-0 trace bubbles, as discussed above.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, high productivity can be achieved even at low reaction temperatures and shorter reaction times. 15,16 In the literature, several studies can be found on the use of sonochemistry for the preparation of different materials, such as ZnO, 17 22 However, sonochemistry has not been applied for the synthesis of zinc borates. Our group has published two studies on the production of zinc borates via the ultrasonic route.…”
Section: Introductionmentioning
confidence: 99%